IN SILICO ANALYSIS OF SNPs IN HUMAN OBESITY RELATED GENE, SLC6A14 (SOLUTE CARRIER FAMILY 6 (AMINO ACID TRANSPORTER), MEMBER 14) - RAJAN KUMAR SINGH,; PERMENDRA KUMAR,; K. MAHALINGAM, (International Journal of Pharma and Bio Sciences, 2016)
The SLC6A14 gene is an exciting novel candidate for human obesity. Sequence homology based computational algorithms: PolyPhen 2.0, SIFT dbSNP138 and I-Mutant 2.0 were used to identify the potentially deleterious non-synonymous single nucleotide polymorphisms (nsSNPs) of this gene. There were five nsSNPs (rs369615885, rs199531433, rs200351649, rs182839907 and rs376518536) found to give the significant results with these tools. Furthermore, stereochemical properties of the predicted models were analyzed by homology modeling and PROCHECK analysis. The present study may suggest that predicted nsSNPs along with functional analysis of in vitro and in vivo lead to be a better understanding of the causal effect of SLC6A14 gene on the obesity phenotype and contribute to the development and succession of human obesity.